Monitoring the Impact of Floods on Water Quality Using Optical Remote Sensing Imagery: The Case of Lake Karla (Greece) - (:unkn) unknown (My University, 2024)
This study investigates the performance of published bio-optical remote sensing indices/ algorithms for monitoring water quality changes in Lake Karla, Greece, caused by Storm Daniel after the September 2023 flooding event. Commonly applied indices were utilised to estimate chlorophyll-a (Chl-a) and total suspended solids (TSS) using Sentinel-2 high-resolution optical imagery. In situ measurements were undertaken and water samples were collected during the pre-flooding period, post-flooding, and one-year post-flood, providing a basis for validating the remote sensing models. Monitoring results showed that most physicochemical parameters changed considerably. Chl-a and TSS were estimated by testing five and seven indices, respectively. Regarding the Chl-a estimation, the NDCI and 2-BDA indices outperformed other models, having high correlations with in situ Chl-a measurements and effectively following the in situ Chl-a temporal trends. Among the TSS indices, NDWI and TUR-IND demonstrated better performances, effectively capturing the variations in suspended solids. Overall, this study highlights the potential of Sentinel-2 imagery in assessing water quality changes, particularly in response to flooding events. It is an exploratory approach to assess the feasibility of utilising optical satellite data for evaluating the environmental impacts of natural disasters on lake water quality and supports decision-making in environmental management. Additionally, it identifies potential challenges and considerations that must be addressed to ensure effective application.
Perivolioti, T.-M.; Zachopoulos, K.; Zioga, M.; Tompoulidou, M.; Katsavouni, S.; Kemitzoglou, D.; Terzopoulos, D.; Mouratidis, A.; Tsiaoussi, V. Monitoring the Impact of Floods on Water Quality Using Optical Remote Sensing Imagery: The Case of Lake Karla (Greece). Water 2024, 16, 3502. https://doi.org/10.3390/w16233502
Keywords: Υγρότοποι; Λίμνες; Φυσικοχημική ανάλυση